Pilot Testing of Intervention Protocols to Prevent Pneumonia among Nursing Home Residents - Quagliarello, Vincent (2009)
OBJECTIVES: To test intervention protocols for feasibility, staff adherence and effectiveness in reducing pneumonia risk factors (i.e., impaired oral hygiene, swallowing difficulty) in nursing home residents. DESIGN: Prospective study. SETTING: Two nursing homes. PARTICIPANTS: Fifty-two nursing home residents. INTERVENTIONS: Thirty residents with impaired oral hygiene were randomly assigned to manual oral brushing + 0.12% chlorhexidine oral rinse at different frequencies daily. Twenty-two residents with swallowing difficulty were randomly assigned to upright feeding positioning, teaching swallowing techniques, or manual oral brushing. All protocols were administered over 3 months. MEASUREMENTS: Feasibility was assessed monthly and defined as high if the protocol took < 10 minutes to administer. Adherence was assessed weekly and defined as high if full staff adherence was demonstrated in >75% of assessments. Effectiveness for improved oral hygiene (i.e., reduction in oral plaque score) and swallowing (i.e., reduction in cough during swallowing) was assessed at 3 months compared to baseline. RESULTS: Daily manual oral brushing + 0.12% chlorhexidine rinse demonstrated high feasibility, high staff adherence and effectiveness in improving oral hygiene (p<0.001 compared to baseline); this combination administered twice per day showed the highest plaque score reduction. Daily manual oral brushing and upright feeding positioning demonstrated high feasibility, high staff adherence, and effectiveness in improving swallowing. CONCLUSION: Manual oral brushing, 0.12% chlorhexidine oral rinse, and upright feeding positioning demonstrated high feasibility, high staff adherence, and effectiveness in pneumonia risk factor reduction. A protocol combining these components warrants testing for its ability to reduce pneumonia among nursing home residents.